Pre-participation Cardiovascular Screening of Elderly Wrestlers - Farahani, Ali Vasheghani (Tehran University of Medical Sciences, 2010)
PURPOSE: Sudden death of a competitive athlete is a tragedy that is usually caused by a previously unsuspected cardiovascular disease. The aim of this study was to clarify the role of noninvasive testing in pre-participation cardiovascular evaluation of elderly wrestlers. METHODS: We included 63 Iranian elderly wrestlers who participated in Tehran international elderly wrestlers’ preparation camping by census method. A questionnaire including past medical and family history as well as coronary risk factors was filled out and then a complete physical examination of the cardiovascular system was done by an internist for all wrestlers. Electrocardiogram (ECG), complete echocardiographic examination and then symptom limited exercise test were performed and reported by the cardiologists who did not know the other examinations results. RESULTS: Exertional dyspnea and typical chest pain (FC=I or II) were present in 5% and 1.7% of the examinees, respectively. There were one or more risk factors in 64.5% of the cases. Cardiovascular examination revealed abnormal heart sounds in 27.1%. ECG showed ischemic changes in 13.6% and premature atrial contractions and premature ventricular contractions in 11.4%. Echocardiography showed mild left ventricular systolic dysfunction in 3.4%, regional wall motion abnormality in 8.5%, valvular disease in 32.3%, diastolic dysfunction in 45.7%, and left ventricular hypertrophy in 16.9% of the cases. Exercise test results were negative, equivocal, positive and highly positive in 70.4%, 15.8%, 5.2%, and 8.6% of cases, respectively. CONCLUSION: Beside physical examination, pre-participation screening of elderly wrestling athletes with ECG and exercise testing is feasible and recommended in the presence of coronary risk factors or cardiac symptoms. Echocardiography can also be recommended to detect other relevant abnormalities when there is a clue in the standard history, physical examination or ECG.